Tissue Type Differences in ABCB1 Expression and Paclitaxel Tissue Pharmacokinetics in Patients With Esophageal Cancer - van Eerden, Ruben A. G.; van Doorn, Leni; de Man, Femke M.; Heersche, Niels; Doukas, Michail; van den Bosch, Thierry P. P.; Oomen-de Hoop, Esther; de Bruijn, Peter; Bins, Sander; Ibrahim, Eman; Nikkessen, Suzan; Friberg, Lena E.; et al. (Frontiers in Pharmacology, 2021)
Abstract Background: Data from previous work suggests that there is no correlation between systemic (plasma) paclitaxel exposure and efficacy in patients treated for esophageal cancer. In this trial, we investigated ABC efflux transporter expression and intratumoral pharmacokinetics of paclitaxel to identify changes which could be a first sign of chemoresistance. Methods: Patients with esophageal cancer treated with paclitaxel and carboplatin (±concomitant radiotherapy) were included. During the first and last cycle of weekly paclitaxel, blood samples and biopsies of esophageal mucosa and tumor tissue were taken. Changes in paclitaxel exposure and expression of ABCB1 (P-glycoprotein) over time were studied in both tumor tissue and normal appearing esophageal mucosa. Results: ABCB1 was significantly higher expressed in tumor tissue compared to esophageal tissue, during both the first and last cycle of paclitaxel (cycle 1: P<0.01; cycle 5/6: P=0.01). Interestingly, ABCB1 expression was significantly higher in adenocarcinoma than in squamous cell carcinoma (P<0.01). During the first cycle, a trend towards a higher intratumoral paclitaxel concentration was observed compared to esophageal mucosa concentration (RD:43%; 95%CI: -3% to 111%; P=0.07). Intratumoral and plasma paclitaxel concentrations were significantly correlated during the first cycle (AUC0-48h: r=0.72; P<0.01). Conclusions: Higher ABCB1 expression in tumor tissue, and differences between histological tumor types might partly explain why tumors respond differently to systemic treatment. Resistance by altered intratumoral paclitaxel concentrations could not be demonstrated because the majority of the biopsies taken at the last cycle of paclitaxel did contain a low amount of tumor cells or no tumor. Clinical Trial Registration: NL5990 (www.trialregister.nl)